Let's-Read-and-Find-Out Science, (Stage 1) : Dinosaurs : Big and Small - Kathleen Weidner Zoehfeld (China Harper collins Publisher, 2002)
Read and find out about dinosaurs big and small in this colorfully illustrated nonfiction picture book. Some dinosaurs were big. How big? As long as four school buses in a row, as heavy as sixteen elephants. Some dinosaurs were small. How small? Read and find out in this clear and appealing science book for early elementary age kids, both at home and in the classroom. This is a Level 1 Let's-Read-and-Find-Out, which means the book explores introductory concepts perfect for children in the primary grades. The 100+ titles in this leading nonfiction series Top 10 reasons to love Books in this series support the Common Core Learning Standards, Next Generation Science Standards, and the Science, Technology, Engineering, and Math (STEM) standards. Let's-Read-and-Find-Out is the winner of the American Association for the Advancement of Science/Subaru Science Books & Films Prize for Outstanding Science Series.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction